Application of Behavioural Model to Disaster Preparedness in A Developing Country Malaysia: An Overview - Nurizyani Azhar; Lutfan Jaes; Norizan Rameli; Asyraf Maula; Yuslizar Kamaruddin; Muhaymin Hakim Abdullah (Journal of Social Transformation and Regional Development, 2022)
The world was recently shocked by an outbreak of a deadly virus. The recent emergence of the COVID-19 pandemic has increased societal stress levels through disruptions in daily work routines, adoption of new norms, low viral predictability, loss of source of income, death of loved ones, long-covid symptom, and subsequently being pushed to cope with a global economic crisis. It is believed that an endemic crisis will have a grave impact on everyone. Therefore, preparedness for disasters at individual, community and organisational levels are important to reduce disaster risk and minimising their impacts. The existing evidence on the application of behavioural coping models on disaster and emergency preparedness is predominantly from developed countries. The purpose of this study is to provide an overview of the existing behavioural models on the subject, and also to present cross cultural issues that may contribute to ways of understanding the community’s coping behaviour during a disaster. Following a discussion of their utility in developing countries such as Malaysia, this paper first discusses how cultural characteristics influence a community’s behaviour to cope with the unprecedented events. It then reviews how behavioural model can be applied to reduce risk- or to cope with the stress of a natural disaster. Future research on behavioural model addressing preparedness needs to focused on developing countries where there is a high probability of lacked coping capacity.